2021
DOI: 10.1017/gmh.2021.14
|View full text |Cite
|
Sign up to set email alerts
|

Teacher stress, anxiety and depression at the beginning of the academic year during the COVID-19 pandemic

Abstract: Background. Faced with the situation of COVID-19, teachers are dealing with new measures, insecurity and a lack of clear guidelines. The aim of this study is to analyse the levels of stress, anxiety and depression of teachers in the north of Spain. Methods. This study was conducted with 1633 teachers from the Department of Education of the Basque Autonomous Community (BAC) and Navarre, all of whom are professionals working in various educational centres, from nursery education to university studies, with an av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
96
3
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(134 citation statements)
references
References 48 publications
9
96
3
5
Order By: Relevance
“…A study that analyzed the levels of stress, anxiety, and depression of teachers in Spain found that 32.2% of the teachers showed a certain degree of depressive symptoms. 29 Other studies with teachers also show similar results, highlighting the mental health impacts of the pandemic. 22,30 Many negative psychological aspects were seen during the pandemic, such as the fear of infection, frustration, boredom, and inadequate information.…”
Section: Discussionmentioning
confidence: 55%
“…A study that analyzed the levels of stress, anxiety, and depression of teachers in Spain found that 32.2% of the teachers showed a certain degree of depressive symptoms. 29 Other studies with teachers also show similar results, highlighting the mental health impacts of the pandemic. 22,30 Many negative psychological aspects were seen during the pandemic, such as the fear of infection, frustration, boredom, and inadequate information.…”
Section: Discussionmentioning
confidence: 55%
“…Reportedly, teachers had symptoms of stress, anxiety, and depression during the pandemic. This was especially evident among female teachers and those who had children (6). Their age, job stability, level of education, information sources, and level of apprehension also influenced their symptoms (2,7).…”
Section: Introductionmentioning
confidence: 94%
“…Mondragon, N.B. Santxo, N. Ozamiz-Etxebarria досліджували вияви стресу, напруженості і депресії у вчителів на початку академічного року в період пандемії COVID-19 [20].…”
Section: і насамкінець проаналізуємо організаційно-психологічні умови та програми для забезпечення психологічного здоров'я персоналу освіunclassified